2, 3-Butanediol production using soy-based nitrogen source and fermentation process evaluation by a novel isolate of Bacillus licheniformis BL1. Issue 10 (2nd November 2021) - Das, Arijit; Prakash, Gunjan; Lali, Arvind M.
Abstract: 2, 3-Butanediol (2, 3-BDO) has varied applications in chemical, pharmaceutical, & food industry. Microorganisms belonging to Klebsiella, Enterobacter & Serratia genera are well-known producers of 2, 3-BDO. However, they have limited usage in industrial-scale owing to their pathogenic nature. A nonpathogenic soil isolate identified as Bacillus licheniformis ( BL1 ) was thus investigated for 2, 3-BDO production. Soy flakes, soy flour, defatted soy, and soybean meal-based hydrolysates replaced yeast extract and peptone as nitrogen sources. Defatted soy flakes and soybean meal hydrolysate led to an equivalent 2, 3-BDO yield and productivity as compared to that of Yeast Extract and peptone. The pH and oxygen variation influenced the proportion of various products of the mixed acid-butanediol pathway. Further, the batch mode fermentation with soy hydrolysate and optimized process parameter resulted in 2, 3-BDO titer, yield and productivity of 11.06 g/L, 0.43 g/g and 0.48 g/L h respectively. Glucose concentration above 5% was inhibitory and led to reduction in the specific growth rate of BL1 in batch cultivation. Intermittent glucose feeding in fed-batch mode overcame this substrate limitation resulting in increased titers (49.8 g/L) and productivity (0.62 g/L h). Modified medium containing soy hydrolysate as nitrogen source with fermentation process optimization resulted in 67% decrease in medium cost for 2, 3-BDO production.